A structure‐based strategy toward the development of novel candidates for antimycobacterial activity: Synthesis, biological evaluation, and docking study. (7th December 2017) - Li, Linhu; Jin, Yuanyuan; Wang, Bin; Yang, Zhaoyong; Liu, Mingliang; Guo, Huiyuan; Zhang, Jun; Lu, Yu
Abstract : Bacterial resistance to most of the available antibiotics has stimulated the discovery of novel efficacious antibacterial agents. Bedaquiline is first of its type that has been specifically introduced for the management of MDR‐TB in combination with other drugs. In this study, a series of isoniazid/ethambutol/pyrazinamide/‐quinoline conjugates based on the structures of bedaquiline were designed and synthesized. Biological activity tests revealed that some of isoniazid/ethambutol/quinoline conjugates have useful antibiotic activity against MTB H37Rv (MIC: 2.0–8.0 μg/ml). Furthermore, molecular docking calculations were performed for the most potent inhibitor to show its binding interactions within the active site of the possible target protein. Overall, these compounds represent novel valuable starting point with potent antimycobacterial activity and deserve further structural modifications. Abstract : In this study, a series of isoniazid/ethambutol/pyrazinamide/quinoline conjugates based on the structures of bedaquiline were designed and synthesized. Biological evaluation indicated that some of isoniazid/ethambutol/quinoline conjugates have useful activity against MTB H37Rv (MIC: 2.0–8.0 μg/ml).